No evidence that plant–soil feedback effects of native and invasive plant species under glasshouse conditions are reflected in the field. (September 2016) - Schittko, Conrad; Runge, Christian; Strupp, Marek; Wolff, Sascha; Wurst, Susanne
Summary: Plant–soil feedback (PSF) may affect above‐ground higher trophic levels in glasshouse experiments, but evidence from field studies on the relevance of these multitrophic interactions for plant performance is lacking. Therefore, we examined whether PSF effects of several native and invasive plant species occur also in the field and influence plant damage by above‐ground herbivores. Root zone soil from an abandoned urban field was used as inocula for the PSF experiment. First, we grew eight urban grassland plant species (five natives and three invasive species) separately in a glasshouse, with soil biota communities conditioned by the respective species itself ('home soil') or by a mixture of all other species ('foreign soil'). After 13 weeks, one cohort of the plants was placed on an urban field in Berlin to assess damage by naturally colonizing herbivores, while another cohort of the plants stayed in the glasshouse. We observed that the extent of the PSF effects differed between the field and glasshouse cohorts of plants. While we found positive PSF responses for five of the eight plant species in the glasshouse, we found no PSF effects in the field. Further, there was no trend that invasive or native species differed in the direction or extent of PSF responses. Concerning the leaf damage by herbivores of the field plants, we found no evidence that the soil history (home vs. foreign soil) affected the effects of above‐ground herbivores on the plants. Synthesis . We conclude that PSF effects are more likely to be found under glasshouse conditions. In the field, PSFs seem to play a minor role for the selected urban grassland species. More generally, our study highlights the need to focus on PSFs under natural conditions and in natural communities (including higher trophic levels), which is often overlooked in PSF research. Abstract : We conclude that PSF effects are more likely to be found under glasshouse conditions. In the field, PSFs seem to play a minor role for the selected urban grassland species. More generally, our study highlights the need to focus on PSFs under natural conditions and in natural communities (including higher trophic levels), which is often overlooked in PSF research.